Contribution of Surface Distributions to Constant-Phase-Element (CPE) Behavior: 3. Adsorbed Intermediates. (10th October 2017) - Alexander, Christopher L.; Tribollet, Bernard; Vivier, Vincent; Orazem, Mark E.
Highlights: Impedance simulations for reactions coupled by adsorbed intermediates. Corresponding faradaic impedance shows dispersion at low frequencies. Low-frequency dispersion caused by potential dependence of the faradaic impedance. Low-frequency dispersion caused by surface distributions of rate constants. Contribution of frequency dispersion reduced by use of small electrodes. Abstract: The influence of surface distributions on rates of heterogeneous reactions coupled by adsorbed intermediates was studied to determine whether this form of surface heterogeneity can provide a physical explanation for constant-phase-element behavior. Results obtained from finite-element simulations on disk and recessed disk electrodes show that there are two components that give rise to frequency dispersion. Frequency dispersion occurs due to geometry-induced nonuniform current distributions which leads to a complex ohmic impedance. The effects of geometry-induced frequency dispersion may be mitigated by use of small electrodes. Frequency dispersion also occurs due to the potential dependence of the faradaic impedance. The characteristic frequency associated with this form of frequency dispersion is not dependent on disk radius, but the contribution of frequency dispersion associated with reactions coupled by adsorbed intermediates may be reduced with the use of small electrodes.